If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2u + -11 = 5(u + 2) Reorder the terms: -11 + 2u = 5(u + 2) Reorder the terms: -11 + 2u = 5(2 + u) -11 + 2u = (2 * 5 + u * 5) -11 + 2u = (10 + 5u) Solving -11 + 2u = 10 + 5u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-5u' to each side of the equation. -11 + 2u + -5u = 10 + 5u + -5u Combine like terms: 2u + -5u = -3u -11 + -3u = 10 + 5u + -5u Combine like terms: 5u + -5u = 0 -11 + -3u = 10 + 0 -11 + -3u = 10 Add '11' to each side of the equation. -11 + 11 + -3u = 10 + 11 Combine like terms: -11 + 11 = 0 0 + -3u = 10 + 11 -3u = 10 + 11 Combine like terms: 10 + 11 = 21 -3u = 21 Divide each side by '-3'. u = -7 Simplifying u = -7
| x-7=4x+1 | | 8x+18=3x+-7 | | 6x+1=4x-13 | | (x-15)-(2x-13)=1 | | 6x(6x)+5(3x(3x)-x)-3x= | | 4x-3+90=180 | | f(x)=500-75x | | 3x(x-2)=24 | | 3x(x-2)=23 | | (1+0.05)4= | | A=0.5(b+12)5 | | 2x-6+2x-9=180 | | 9+x+7+x=50 | | 2-3(x-5)=20 | | 23x=10x+5 | | 4-y=230 | | 4x=18+4 | | 10x=5x+2 | | 5(3)=3645 | | (11x*2/3)*(11x*-2/3) | | 19-a=-2a | | 2x-27=95 | | 10-6x=20-26x | | 3x^2-4x+119=0 | | 70-2x=85-3x | | 4/d=12 | | y^2-8y+154=0 | | 4x-32=3x+10 | | -0.33-m=-0.11m+0.037-0.33m | | -40=(x-10) | | 10-4x=30-44x | | -2(-2)-4(-2)= |